PEMBANGUNAN EKONOMI DESA DI KABUPATEN BIMA: PERSPEKTIF PERBANDINGAN TEORI AS-SYAITIBI DAN IBNU KHALDUN - Handayani, Sahfira; Indriani, Ira; Nurhayati, Nurhayati; Eka, Eka; Setiawati, Nirwana; Sulastri, Gita; Junari, Junari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to compare the perspectives of two renowned Muslim scholars in the field of economics, Ibn Khaldun and As-Syaitibi, regarding the allocation of village funds in Bima Regency. The research method used is qualitative, involving the collection of descriptive data through interviews, observations, and documentation. The results of this study reveal that the theory most commonly used in the allocation of village funds in Bima Regency is As-Syaitibi's theory, specifically the maqasid shariah theory which includes five key points: the preservation of religion, life, intellect, lineage, and wealth, as well as the theory regarding the three categories of needs that must be met (primary, secondary, and tertiary). However, this does not mean that Ibn Khaldun's theory is not used in the allocation of village funds; it is just less prominent, particularly in aspects such as social change, economic development, and human civilization. The findings of this study contribute to understanding the extent to which Islamic economic systems are used in the allocation of village funds, particularly in Bima Regency. The limitation of this research is that our data is still limited due to the fact that only a few places were included in our observations. Future research needs to collect more data from a wider range of locations.